The Influence of Competitiveness on Community Purchase Interest at TOKMA Supermarket in Cibitung - Shocky Lie (Yayasan Putra Adi Dharma, 2024)
In the midst of global competition, enhancing competitiveness is imperative for countries to avoid marginalization in the global arena. This study focuses on the influence of competitiveness on consumer purchase intentions at TOKMA Department Store in Cibitung, Bekasi. The research examines the relationship between competitiveness and purchase intentions, considering factors such as pricing strategies, product variety, and customer satisfaction. The findings indicate that TOKMA Department Store exhibits competitive pricing and a wide range of products, influencing consumer purchase intentions positively. However, the study also reveals areas for improvement, particularly in enhancing product quality and customer experience. Overall, the research highlights the importance of competitiveness in attracting customers and driving purchase decisions in the retail sector